Characterisation of Miswak (Salvadora persica) fibre-reinforced polylactic acid composites prepared by twin screw extrusion - Shafi, Ayu Rafiqah; Abdan, Khalina; Salit @ Sinon, Mohd Sapuan; Ali, Radzi (Universiti Putra Malaysia Press, 2024)
Processing of polymer composites employing fibres from sustainable sources as reinforcement has drastically grown in recent years. This research used Miswak fibres (MF) and polylactic acid (PLA) as the main materials for composite processing. Natural fibres typically include a hydroxyl group (-OH), which makes them hydrophilic. In contrast, the hydrophobic nature of polymer matrices causes them to naturally repel water. This problem was resolved by chemically altering the surface of natural fibres using a 2 wt% sodium hydroxide (NaOH) solution. In this paper, the effect of alkaline treatment has been proven by performing chemical analysis, tensile properties, thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) to analyse the influence of treated MF content on composite characteristics. The results revealed that biocomposites with modified miswak fibres exhibited better properties than untreated miswak fibres-reinforced polymer biocomposites. Treated MF/PLA composites showed an increase in tensile strength of 52.9% and tensile modulus of 8.16%. From the chemical composition test, lignin composition was reduced from 5.09% to 3.06% and hemicellulose from 28.12 to 10.62% after MF was treated. Meanwhile, thermal properties for both TGA and DSC